The environment and dry eye—manifestations, mechanisms, and more - Patel, Sneh; Mittal, Rhiya; Kumar, Naresh; Galor, Anat (Frontiers in Toxicology, 2023)
Dry eye disease (DED) is a multifactorial condition that often presents with chronic symptoms of pain (that can be characterized as “dryness,” “burning,” and “irritation,” to name a few) and/or fluctuating or poor-quality vision. Given its multifactorial nature, several pathophysiologic mechanisms have been identified that can underlie symptoms, including tear film, ocular surface, and/or corneal somatosensory nerve abnormalities. Research has focused on understanding how environmental exposures can increase the risk for DED flares and negatively impact the tear film, the ocular surface, and/or nerve health. Given that DED is a common condition that negatively impacts physical and mental functioning, managing DED requires multiple strategies. These can include both medical approaches and modulating adverse environmental conditions, the latter of which may be a cost-effective way to avoid DED flares. Thus, an understanding of how environmental exposures relate to disease is important. This Review summarizes research on the relationships between environmental exposures and DED, in the hope that this information will engage healthcare professionals and patients to consider environmental manipulations in their management of DED.